The relationship between cadmium exposure and preeclampsia: a systematic review and meta-analysis - Li, Chu; Luo, Jiamin; Yang, Yunping; Wang, Qianqian; Zheng, Yanmei; Zhong, Zixing (Frontiers in Medicine, 2023)
Background Cadmium (Cd) is a heavy metal associated with several human disorders. Preeclampsia is a major cause of maternal mortality worldwide. The association between maternal Cd exposure and preeclampsia remains elusive. Methods To better understand this relationship, we conducted a systematic review and meta-analysis of eligible studies from five databases (PubMed, Embase, Web of Science, Scopus, and CNKI) from their inception to September 10, 2022. The quality of these studies was evaluated using the Newcastle-Ottawa quality assessment scale (NOS). We use random-effects models to calculate overall standardized mean differences (SMDs) and 95% confidence intervals (CIs). Sensitivity analyses were performed to assess the robustness of our results. We also evaluated publication bias using Egger’s and Begg’s tests. Additionally, we conducted meta-regression and sub-group analyses to identify potential sources of heterogeneity between studies. Results Our analysis included a total of 17 studies with 10,373 participants. We found a significant association between maternal cadmium exposure and the risk of preeclampsia (SMD 0.27, 95% CI 0.09–0.44, p < 0.01). No significant publication bias was detected in Begg’s or Egger’s tests. Meta-regression suggested that geographical location, year of publication, cadmium samples, sample size, and measurement methods did not contribute to heterogeneity between studies. Conclusion Our findings suggest that maternal blood cadmium levels are associated with an increased risk of preeclampsia. In contrast, the pregnant women’s urine or placental levels of cadmium may not suggest preeclamptic risk during pregnancy. Further high-quality clinical studies and animal experiments are needed to understand this association better. Systematic review registration PROSPERO, https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=361291, identifier: CRD42022361291.